Monitoramento de reator enzimático para produção de ampicilina - Padua, Thiago Faggion de (2008)
This work is part of a research project in DEQ-UFSCar (Department of Chemical Engineering at Federal University of São Carlos, Brazil). The focus is to develop a competitive industrial enzymatic process to obtain semi-synthetic β- Lactam antibiotics. This process rivals with the conventional one, which uses toxic solvents and generates non-recyclable residues. Thus, the increasing rigor of environmental regulations is an important driving force for the research. The enzymatic production of ampicillin, in aqueous medium, uses a derivate from an acyl donor (in this work, D-phenylglycine methyl ester, PGME) and 6-aminopenicillanic acid (6-APA). Penicillin G acylase (PGA) is usually the biocatalyst for this process. Unfortunately, PGA acts either as transferase, producing ampicillin (AMP), or as hydrolase, producing D-phenylglycine (PG) from PGME (and from ampicillin). This is a series-parallel reaction scheme, with the antibiotic being the desired intermediate product. This work studied the use of multivariate calibration in a spectrophotometer for on-line monitoring the enzymatic synthesis reactor. High Performance Liquid Chromatography (HPLC) is the usual analytical procedure, which is time demanding, expensive and generates amounts of disposals. Multivariate calibration, on its turn, only uses dilutions of reactor samples and a spectrophotomer (with UV detector). Some multivariate calibration techniques (SPA, PCR, PLS) were tested and compared. They didn t show representative differences in cross-validations or in test data. The work also focused the automation of a reactor and its accessories, where the enzymatic production of ampicillin and 6-APA (after Penicillin G enzymatic hydrolysis) takes place. The software was implemented in LabVIEW (National Instruments), which controls the Automatic Sampler (AS) for multivariate analysis, among other equipments. The development of this system provided a real-time concentration response from the reactor, for all chemical species. Following an optimal trajectory in the enzymatic reactor by adding reactants is one of the most important strategies to reach a competitive process. Hence, the concentration sensor represents an important step for the feasibility of the enzymatic process, because it could be used to monitor and control the concentrations of substrates during the industrial feed-batch. Several assays, among then batch and fed-batch runs, were done and many modifications on the experimental scheme were implemented or proposed. Some of these assays could be treated as validation of monitoring software and concentration sensor, which showed good results.